The current state of biodiesel in the world - Лютий, О.С.; Бойченко, С.В.; Аксьонов, О.Ф. (Proceedings of National Aviation University (archive), 2009)
In report examined basic aspects changings on world’s oil and oil products market also preservation of the environment which were brought to find alternative kinds of fuels, stated basic way to develope produce biodiesel fuel in the world.